2018
DOI: 10.1017/s0272263118000050
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Processing Instruction and Traditional Instruction on L2 Online Processing of the Causative Construction in French: An Eye-Tracking Study - Corrigendum

Abstract: The above article (Wong & Ito, 2017) published with multiple errors: Page 9, under the section subheading "PI training", stated that "A total of 12 sentences containing the verb faire in the causative construction and 12 sentences with the verb faire in the noncausative construction..." The sentence should read "A total of 24 sentences containing the verb faire in the causative construction and 24 sentences in the noncausative construction..." Page 10, under the section subheading "TI training", stated that "A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(54 citation statements)
references
References 1 publication
5
47
2
Order By: Relevance
“…Although this change in the eye-movements provided novel evidence for the effect of PI on online sentence processing, Wong and Ito (2018) reported that the timing of the shift was not as early as predicted. The infinitive verb that follows the main verb (e.g., faire after fait in example [1]) is the first critical grammatical cue that differentiates the causative structure from the noncausative structure.…”
Section: Background and Motivationmentioning
confidence: 84%
See 2 more Smart Citations
“…Although this change in the eye-movements provided novel evidence for the effect of PI on online sentence processing, Wong and Ito (2018) reported that the timing of the shift was not as early as predicted. The infinitive verb that follows the main verb (e.g., faire after fait in example [1]) is the first critical grammatical cue that differentiates the causative structure from the noncausative structure.…”
Section: Background and Motivationmentioning
confidence: 84%
“…Importantly, the eye-tracking data of Wong and Ito (2018) also demonstrated the change in online responses to the input in the PI group but not in the TI group. Despite the small but significant increase in the picture-selection accuracy, the TI group maintained the same pattern of eye-movements, that is, the bias toward the (first noun = agent) picture, till the end of the sentence.…”
Section: Background and Motivationmentioning
confidence: 95%
See 1 more Smart Citation
“…A new research area in PI is now expanding the scope of the methodology to not only compare accuracy scores as in previous studies but also to measure processing behaviours using eye-tracking. Only two studies thus far (Wong and Ito, 2017;Lee and Doherty, 2019) have considered the use of eye-tracking to measure the effectiveness of PI; both investigate a different processing principle (i.e. the First Noun Principle) than the one under investigation in this study.…”
Section: Input Processing and Processing Instructionmentioning
confidence: 99%
“…These results can be attributed to the positive effects of PI. Wong and Ito (2017) explored the changes in processing patterns between two groups of learners, one group receiving PI and the other receiving TI on the acquisition of the causative construction in French. The results provide evidence for the FNP in eye-movement data, along with beneficial results from PI in the accuracy of picture selection post-instruction, in line with previous offline studies (VanPatten and Wong, 2004).…”
Section: Input Processing and Processing Instructionmentioning
confidence: 99%